Analisis kualitas air Sungai Krueng Aceh berdasarkan indeks pencemaran untuk pengelolaan lingkungan berkelanjutan - Kurniawan, Rizky; Maysitah, Maysitah; Irhamni, Irhamni; Ardila, Mutia; Kurniawan, Hadi (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2026)
The Krueng Aceh River is an important water resource vulnerable to anthropogenic pressures from urban activities and domestic waste. This study aimed to evaluate water quality based on physicochemical parameters and determine its status using the Pollution Index (PI). A quantitative descriptive approach with grab sampling was applied at three stations (upstream, midstream, downstream). Laboratory analyses followed Indonesian National Standards (SNI), and water quality assessment referred to Class II standards. Results showed neutral pH (7.0–7.1), low TSS (0.0127–0.0407 mg/L) and TDS (2.06–2.29 mg/L), and increasing sulfate from upstream to downstream (5.73–107.40 mg/L), all below threshold limits. Heavy metals (Fe, Zn, Cu, Pb, Ni) were below detection limits. In contrast, ammonia exceeded the standard at all stations, with the highest concentration at S2 (0.3582 mg/L), making it the dominant factor influencing water quality. The PI indicated good quality at S1 (0.9856) and lightly polluted conditions at S2 (1.6175) and S3 (1.1789). These findings suggest potential water quality degradation, highlighting the need for sustainable management through pollutant load control and regular monitoring.